2000
DOI: 10.1115/1.1432991
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Based Collaborative Optimization

Abstract: In this research a Collaborative Optimization (CO) approach for multidisciplinary systems design is used to develop a decision based design framework for non-deterministic optimization. To date CO strategies have been developed for use in application to deterministic systems design problems. In this research the decision based design (DBD) framework proposed by Hazelrigg [1,2] is modified for use in a collaborative optimization framework. The Hazelrigg framework as originally proposed provides a single level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 12 publications
0
58
0
Order By: Relevance
“…When γ = |φ/α|, the radius is identical to the original radius , and when γ = 1, the radius becomes in Eq. (6). As shown in Fig.…”
Section: B Utilization Of Slope Informationmentioning
confidence: 80%
See 2 more Smart Citations
“…When γ = |φ/α|, the radius is identical to the original radius , and when γ = 1, the radius becomes in Eq. (6). As shown in Fig.…”
Section: B Utilization Of Slope Informationmentioning
confidence: 80%
“…When the next target for the engineering problem (T * + ) is obtained by solving the modified enterprise problem, the gradient of the utility function, denoted as φ, is also obtained. If the engineering problem returns the same response (T * − ) and |φ| ≤ |α|, then the constraint radius may be increased up to with the gradient ratio = |α/φ| (6) An updated target (T * + γ ) is assigned to the engineering problem and the engineering problem returns R as response, where γ is the step size for updating the new radius of the constraint that takes a value |φ/α| < γ ≤ 1. When γ = |φ/α|, the radius is identical to the original radius , and when γ = 1, the radius becomes in Eq.…”
Section: B Utilization Of Slope Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…McAllister et al [151] present a multiobjective approach using linear physical programming. Available robust design formulations incorporate the decision-based models of Gu et al [152] and McAllister and Simpson [28], the implicit uncertainty propagation method of Gu et al [153], and the fuzzy computing models of Huang et al [154]. Zadeh and Toropov [118] integrated multiple model fidelities into CO for an aircraft design problem.…”
Section: Collaborative Optimization (Co)mentioning
confidence: 99%
“…There has been a number of efforts to integrate customer preference information in engineering design, e.g., Donndelinger and Cook, 1 Besharati, et al, 2,3 Li and Azarm, 4 Wassenaar and Chen, 5 Cooper, et al, 6 Gu, et al, 7 Michalek, et al 8 They have demonstrated that a relationship exists between marketing and engineering in the enterprise. In this article the enterprise is defined as the organization that designs and produces an artifact to maximize its utility (e.g., profit).…”
Section: Introductionmentioning
confidence: 99%